Main characteristics of urban markets in Africa - Zoma, Vincent; Dahani , Issaka (International Journal of Scientific Research and Management (IJSRM), 2022)
Urban markets influence socially and economically in cities around the world, and imprint an obvious dynamic of development. However, their characteristics very often differ from one geographical area to another. Thus, this article, based on a literature review, aims to study the characteristics of markets in African cities. This research reveals that the characteristics of these markets on the African continent depend on their typologies and the arrangements made there. In terms of spatial distribution, each market is the center of a circle whose radius varies according to its importance and may be, depending on its size, a distribution or collection market. In general, they are characterized by two main types of market infrastructure, namely markets and shopping centers. In addition, the mismatch between the available space and the growth of the markets is at the origin of a remarkable spatial pressure and the interventions of the municipalities are generally very limited by the lack of technical and financial means.